CP-096 Feasibility study on implementation of dose banding in a teaching hospital. (24th March 2015) - Fargier, E; Durand, M; Federspiel, I; Desruet, M; Lemoigne, A; Allenet, B; Foroni, L
Abstract : Background: Dose banding (DB) is a system whereby, through agreement between prescribers and pharmacists, chemotherapy doses calculated on body surface area (BSA) are rounded up or down to predetermined standard doses (SD) with a variance limit of ±5%. In our hospital, over 30, 000 chemotherapy preparations are made per year. Implementation of DB could reduce patient waiting time and improve capacity planning of our cytotoxic preparation unit (CPU). Purpose: To conduct a feasibility study on the implementation of DB in our CPU. Material and methods: Phase I – literature review of DB: to identify selection criteria and method of assigning dose bands. Phase II – retrospective analysis of doses prepared in CPU in 2013: to identify candidate cytotoxic drugs and select SD. Results: In accordance with the literature review, drugs were selected using the following criteria: frequency of preparation above 250 preparations per year, sufficient long-term physicochemical stability after reconstitution and opportunity for savings. "Target dose" banding was chosen for the selection of SD. In order to guarantee a good turnover, 5 SD should cover at least 60% of preparations. Of the 70 pharmaceutical specialties prepared in our CPU, six candidate drugs were eligible: paclitaxel, 5-fluorouracil (5-FU), cyclophosphamide, gemcitabine, cytarabine, calcium folinate. A simulation was made with paclitaxel, 5-FU bolus injection (400 mg/m²), and 5-FU 48 h continuous infusion (2400 mg/m²) with percentage standardisations of 65% (SD: 105, 120, 135, 150 and 165 mg), 69.5% (DS: 500, 600, 700 and 800 mg) and 79.5% (SD: 3, 500, 3, 900, 4, 300 and 4, 700 mg) respectively. Conclusion: Before implementation, this DB project should be approved by the medical staff and some practical constraints such as software, system management, storage, control should be developed. On the other hand, the status of these preparations has not been clearly established by the health authorities in France. They can be considered hospital preparations (authorisation request, statement, and compliant with Good Manufacturing Practice) or compounded medicines requiring an early prescription. References and/or Acknowledgements: No conflict of interest.